2015
DOI: 10.1186/s12889-015-1950-8
|View full text |Cite
|
Sign up to set email alerts
|

Stages of change of the readiness to quit smoking among a random sample of minority Arab -male smokers in Israel

Abstract: BackgroundDespite advanced smoking prevention and cessation policies in many countries, the prevalence of cigarette smoking among indigenous and some ethnic minorities continues to be high. This study examined the stages of change (SOC) of the readiness to quit smoking among Arab men in Israel shortly after new regulations of free-of-charge smoking cessation workshops and subsidized medications were introduced through primary health care clinics.MethodsWe conducted a countrywide study in Israel between 2012–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 59 publications
4
22
0
1
Order By: Relevance
“…In thet study by Cambell et al between 2003–2004, 39.6%, 43.4%, and 13.9% of 594 Australians were assigned to the pre-contemplation, contemplation, and preparation groups, respectively; these values are similar to those in our study of the Korean population [16]. Daoud et al reported that 61.8%, 23.8%, 14.4% were in the pre-contemplation, contemplation stage, and preparation stage, respectively, among Arab men between 2012–2013 [10]. The preparation group showed the least proportion of less than 15% in all studies.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In thet study by Cambell et al between 2003–2004, 39.6%, 43.4%, and 13.9% of 594 Australians were assigned to the pre-contemplation, contemplation, and preparation groups, respectively; these values are similar to those in our study of the Korean population [16]. Daoud et al reported that 61.8%, 23.8%, 14.4% were in the pre-contemplation, contemplation stage, and preparation stage, respectively, among Arab men between 2012–2013 [10]. The preparation group showed the least proportion of less than 15% in all studies.…”
Section: Discussionsupporting
confidence: 85%
“…: Stanton et al reported that conditions such as anxiety, depression, and substance abuse were related to higher tobacco use, although proportion of cigarette smoking declined significantly over time among adults with no chronic condition [29]. Anxiety, stressful life events, and social support were psychological factors relevant to the stages of changes, as reported by Daoud et al [10]. In our study, although the proportion of people diagnosed with depression was lower in the pre-contemplation group, levels of suicidal ideation and attempted suicide were higher.…”
Section: Discussionmentioning
confidence: 97%
“…A study conducted in Israel found, at the start of treatment 95% of patients were willing to quit smoking. However, when asked about their expectations for abstinence achievement, some patients had very low expectations (Daoud et al., ). These data emphasize the need to assess how determined and motivated a smoker is to quit smoking, aiming to understand the stage at which patients are starting in order to assist them at each stage of the process.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data from periodic telephone surveys in Israel showed that between 2000 and 2008 smoking rates decreased by 3.5 % among adult Jewish men, while an increase of 6.5 % was reported among Arab men [13]. A recent study also showed that Arab male smokers have low intention to stop smoking, with 60 % of current smokers being in the pre-contemplation phase [30]. …”
Section: Discussionmentioning
confidence: 99%